Sensory organization of balance control in children with vestibular migraine and recurrent vertigo of childhood - Li, Xiaofei; Liu, Yalan; Lyu, Yafeng; Li, Yawei; Jian, Huirong; Li, Xiaoyi; Fan, Zhaomin; Wang, Haibo; Zhang, Daogong (Frontiers in Neurology, 2022)
Background Migraine plays an important role in some subgroups of children with recurrent vertigo. Moreover, the migraine component varies from definite to possibly absent as defined in this spectrum of three disorders—vestibular migraine of childhood (VMC), probable VMC (pVMC), and recurrent vertigo of childhood (RVC). However, studies on the sensory organization of balance control in these three disorders are rare. Objective To explore the balance control of children with RVC, VMC and pVMC, when the three sensory systems are challenged. Method A retrospective analysis was performed on 125 children with VMC (18 female and 15 male; aged 11.64 ± 2.74), pVMC (10 female and 8 male; aged 11.78 ± 2.51), and RVC (32 female and 42 male; aged 11.10 ± 2.60). All children in each subtype were divided into groups of children aged ≤ 12 years old and 13–17 years old. Vestibular examination screening and assessment for postural control using the six conditions of the sensory organization test (SOT) were performed. The three primary outcome measures were: equilibrium score (ES), strategy score (SS), and sensory analysis score of the SOT. Results Equilibrium score under six different conditions and composite score increased with age (all P values <0.05). The somatosensory and visual scores also improved with growing (P values <0.05). However, vestibular scores did not increase significantly with age as the other senses did (P>0.05). In the children ≤ 12 year-old group, children with VMC had a significantly higher visual preference score than those with pVMC and RVC (P < 0.05).There was an effect of age on the horizontal HIT. Ocular vestibular evoked myogenic potential (oVEMP), cervical vestibular evoked myogenic potential (cVEMP), and unilateral weakness (UW) values showed no significant difference among three diseases. Conclusion Children with VMC had a higher degree of reliance on visual signals to maintain their balance and a poorer central integration of peripheral information before reaching 12 years of age. In addition, vision may predominate by weakening vestibular function based on visuo-vestibular interactions. It must be noted that peripheral vestibular examinations could not distinguish the three disease subtypes.